MINIMALLY INVASIVE METHODOLOGY FOR SURGICAL TREATMENT OF ODONTOGENIC SINUSITIS - D.S. Avetikov; I.V. Yatsenko; V.N. Нavryliev; V.V. Aipert (Проблеми екології та медицини)
Today, odontogenic sinusitis (OS) occurs in up to 40% of cases among all maxillary sinusitis. At the same time there is an increase in the incidence of OS. This is facilitated by factors such as late medical treatment, improved diagnostic capabilities, an increase in number of dental and especially implantation interventions with the lifting of mucous floor of maxillary sinus. The aim of work was to develop an optimal, sparing surgical option that should lead to a lasting recovery of patients with odontogenic sinusitis. For 5 years, under supervision and treatment, there were 58 patients with hypertension from the age of 20 to 65 years. In 42 of them, the cause of development of exhaust gas was a complication of the tooth extraction operation, which led to perforation of the lower wall of the sinus. In one case out of 42 observed patients with odontogenic sinusitis (OS), the patient did not need to undergo radical surgery on the maxillary sinus lesions. All patients managed to achieve a sustained recovery with minimal surgical intervention, both in bone structures, and in the mucous membrane of the maxillary sinus (MS), nasal cavity and oral cavity. The authors of the article believe that at in case of OS, there is no evidence for radical surgery on MS, and surgical intervention should be organ-preserving. An exception can be made only for cases of OS that is complicated by inflammatory osteomyelitis, orbital and intracranial complications. Patients with OS should be treated in maxillo-facial departments with obligatory consultation of the otorhinolaryngologist, who knows the features of pathological process in MS better than the maxillofacial surgeon. In addition, in OS one should use a set of conservative measures that will help to ensure the compete treatment of the inflamed sinus. Having the opportunity to choose the optimal sparing variant of intervention, one can achieve optimal and steady recovery of patients with OS.